Uncovering the role of oxygen on organic carbon cycling: insights from a continuous culture study with a facultative anaerobic bacterioplankton species (Shewanella baltica) - Maßmig, Marie; Cisternas-Novoa, Carolina; Engel, Anja (Frontiers in Marine Science, 2024)
Deoxygenation is tied to organic carbon (Corg) supply and utilization in marine systems. Under oxygen-depletion, bacteria maintain respiration using alternative electron acceptors such as nitrate. Since anaerobic respiration's energy yield is lower, Corg remineralization may be reduced and its residence time increased. We investigated the influence of oxygen and alternative electron acceptors' availability on Corg cycling by heterotrophic bacteria during a continuous culture experiment with Shewanella baltica, a facultative anaerobic γ-Proteobacteria in the Baltic Sea. We tested six different oxygen levels, from suboxic (<5 µmol L-1 ) to fully oxic conditions, using media (salinity=14 g L-1 ) supplied with high (HighN) or low (LowN) inorganic nitrogen concentrations relative to glucose as labile Corg source. Our results show that suboxia limited DOC (glucose) uptake and cell growth only under LowN, while higher availability of alternative electron acceptors seemingly compensated oxygen limitation under HighN. N-loss was observed under suboxia in both nitrogen treatments. Under HighN, N-loss was highest and a C:N loss ratio of 2.0 indicated that Corg was remineralized via denitrification. Under LowN, the C:N loss ratio under suboxia was higher ( 5.5), suggesting dominance of other anaerobic respiration pathways, such as dissimilatory nitrate reduction to ammonium (DNRA). Bacterial growth efficiency was independent of oxygen concentration but higher under LowN (34±3.0%) than HighN (26±1.6%). Oxygen concentration also affected dissolved organic matter (DOM) cycling. Under oxic conditions, the release of dissolved combined carbohydrates was enhanced, and the amino acid-based degradation index (DI) pointed to more diagenetically altered DOM. Our results suggest bacterial Corg uptake in low-oxygen systems dominated by S. baltica can be limited by oxygen but compensated by high nitrate availability. Hence, suboxia diminishes Corg remineralisation only when alternative electron acceptors are lacking. Under high nitrate:Corg supply, denitrification leads to a higher N:C loss ratio, potentially counteracting eutrophication in the long run. Low nitrate:Corg supply may favour other anaerobic respiration pathways like DNRA, which sustains labile nitrogen in the system, potentially intensifying the cycle of eutrophication. Going forward, it will be crucial to establish the validity of our findings for S. baltica in natural systems with diverse organic substrates and microbial consortia.